New Features on Magnesium Alloys - Alfredo Monteiro, Waldemar (IntechOpen, 2012)
Magnesium alloys have been attractive to designers due to their low density (two thirds that of aluminium), the sixth most abundant on earth, is ductile and the most machinable of all the metals. This has been a major factor in the widespread use of magnesium alloy castings and wrought products, powder metallurgy components, sacrificial anodes for the protection of other metals, tools. The present book, "New Features on Magnesium Alloys", gives us an overview in some special areas of magnesium alloys concerning technological applications and eco-friendly requirements. Each chapter brings us a new facet relating to the magnesium alloy application: magnesium alloys quasicrystals used to magnesium alloys reinforcement; rare earth metals as alloying components in magnesium implants for orthopaedic applications; magnesium alloys surface treatment by applying physical vapor deposition processes; casting magnesium alloys subjected to laser treatment; ductility enhancement on special magnesium alloys; welding and joining processing of magnesium alloys; transport application of magnesium and its alloys.